2006
DOI: 10.1029/2005jd006341
|View full text |Cite
|
Sign up to set email alerts
|

Shortwave radiative closure studies for clear skies during the Atmospheric Radiation Measurement 2003 Aerosol Intensive Observation Period

Abstract: [1] The Department of Energy's Atmospheric Radiation Measurement (ARM) program sponsored a large aerosol intensive observation period (AIOP) to study aerosol during the month of May 2003 around the Southern Great Plains (SGP) Climate Research Facility (CRF) in north central Oklahoma. Redundant measurements of aerosol optical properties were made using different techniques at the surface as well as in vertical profile with sensors aboard two aircraft. One of the principal motivations for this experiment was to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
86
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(103 citation statements)
references
References 41 publications
13
86
0
Order By: Relevance
“…The opposite is valid for O: changes of ω 0 are larger than the corresponding changes of g ( Figure 9; right column). Thus, the corresponding errors of the downwelling diffuse (up to 5%, or ±5 W·m ) and upwelling (up to 3%, or ±3 W·m ) [52]; hence, the errors in calculated downwelling diffuse flux presented here are comparable to these uncertainties.…”
Section: 3radiative Propertiessupporting
confidence: 56%
“…The opposite is valid for O: changes of ω 0 are larger than the corresponding changes of g ( Figure 9; right column). Thus, the corresponding errors of the downwelling diffuse (up to 5%, or ±5 W·m ) and upwelling (up to 3%, or ±3 W·m ) [52]; hence, the errors in calculated downwelling diffuse flux presented here are comparable to these uncertainties.…”
Section: 3radiative Propertiessupporting
confidence: 56%
“…This decrease in diffuse radiation is not fully compensated for by increases in diffuse radiation in other spectral regions where the surface albedo is relatively high, resulting in a net 6.6 Wm −2 decrease in the integrated downwelling irradiance computed using the spectral albedo. From this analysis, it is clear that the use of a spectrally constant surface albedo was an important factor in past studies (e.g., Halthore et al, 2005) that concluded that radiative transfer models overestimated diffuse irradiance for clear sky conditions, in contrast to those studies that used a spectrally varying surface albedo and found no such discrepancy (e.g., Michalsky et al, 2006).…”
Section: Impact Of Spectrally Resolved Surface Albedomentioning
confidence: 49%
“…Radiative closure calculations, in which radiative transfer model calculations are compared to irradiance (flux) or radiance measurements, can serve as a testbed to evaluate the specification of atmospheric column properties retrieved from measurements (including surface conditions, water vapor amount, and aerosol and cloud properties), radiative transfer model calculations, and the radiative measurements themselves (e.g., Michalsky et al, 2006;McFarlane and Evans, 2004;Turner et al, 2004;Halthore and Schwartz, 2000;Mlawer et al, 2000). Previously, studies using data from the Atmospheric Radiation Measurement (ARM) Program have performed such comparisons in the longwave spectral region to refine treatment of the longwave water vapor continuum and to improve the specification of the atmospheric water vapor column.…”
Section: Introductionmentioning
confidence: 99%
“…Aerosol-induced decreases in downward solar radiation have been observed in field experiments (e.g. Leiterer et al (1997) in Germany and Russia, Kanaya et al (2003) at Rishiri Island and Michalsky et al (2006) in Oklahoma) or through analysis of long-term ground and satellite observational data (Lee et al, 2005;Hatzianastassiou et al, 2007;Han et al, 2012). During strong air pollution episodes such as wild fire Grell et al, 2011;Jiang et al, 2012) or dust events , it is calculated that aerosols reduced the shortwave radiation and temperature at the surface, and heated the atmosphere at the top of planetary boundary layer (PBL).…”
Section: Introductionmentioning
confidence: 99%